2015
DOI: 10.3389/fnsyn.2014.00029
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of presynaptic calcium currents and endogenous calcium buffers at the frog neuromuscular junction with two different calcium fluorescent dyes

Abstract: At the frog neuromuscular junction, under physiological conditions, the direct measurement of calcium currents and of the concentration of intracellular calcium buffers—which determine the kinetics of calcium concentration and neurotransmitter release from the nerve terminal—has hitherto been technically impossible. With the aim of quantifying both Ca2+ currents and the intracellular calcium buffers, we measured fluorescence signals from nerve terminals loaded with the low-affinity calcium dye Magnesium Green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 71 publications
5
8
0
Order By: Relevance
“…At the end of loading protocol, all terminals in the proximal part of the nerve trunk had sufficient levels of fluorescence to allow [Ca 2+ ] i recordings. We (in this paper), as well as others have shown that the loading of the fluorescent dye in the nerve ending does not significantly alter the physiological parameters of secretion, such as quantal content and frequency of mEPC (Wu and Betz, 1996; Samigullin et al, 2015). …”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…At the end of loading protocol, all terminals in the proximal part of the nerve trunk had sufficient levels of fluorescence to allow [Ca 2+ ] i recordings. We (in this paper), as well as others have shown that the loading of the fluorescent dye in the nerve ending does not significantly alter the physiological parameters of secretion, such as quantal content and frequency of mEPC (Wu and Betz, 1996; Samigullin et al, 2015). …”
Section: Discussionsupporting
confidence: 55%
“…Our own observations (Samigullin et al, 2015) as well as observations of others (Wu and Betz, 1996) failed to detect any appreciable influence of loaded Ca 2+ probe on the amplitude of the postsynaptic response or on the frequency of the miniature end-plate potentials. Nonetheless we additionally performed control experiments to compare spontaneous endplate currents (mEPC) and quantal release before and after Ca 2+ probe loading.…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…The rate of entry of Ca 2+ into the nerve ending, interaction with the dye, and diffusion in the cytoplasm all affect the rise time of the Ca 2+ transient. The decay time of the fluorescent signal depends on the affinity of the dye, the speed of the Ca 2+ interaction with intracellular buffers, and the removal by ion pumps 35 . The amplitude analysis of Ca 2+ transients can be used to study the influence of various substances on the calcium entry that participates in neurotransmitter release 33 .…”
Section: Representative Resultsmentioning
confidence: 99%